2022
DOI: 10.3390/life12111711
|View full text |Cite
|
Sign up to set email alerts
|

Combined Deep Learning Techniques for Mandibular Fracture Diagnosis Assistance

Abstract: Mandibular fractures are the most common fractures in dentistry. Since diagnosing a mandibular fracture is difficult when only panoramic radiographic images are used, most doctors use cone beam computed tomography (CBCT) to identify the patient’s fracture location. In this study, considering the diagnosis of mandibular fractures using the combined deep learning technique, YOLO and U-Net were used as auxiliary diagnostic methods to detect the location of mandibular fractures based on panoramic images without CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Research has demonstrated that AI-based deep learning methods, such as wavelet-guided deep models, can outperform human observers in terms of diagnostic accuracy [ 21 , 22 ]. While certain deep learning methods have been shown to provide a relatively high diagnosis rate (exceeding 90% using binary classification neural networks [ 20 , 24 ] as well as combined U-Net and YOLOv4 network [ 37 ]), issues such as extended detection time and limited crack information suggest that semantic segmentation methods may offer more detailed and specific information. This can facilitate a more comprehensive understanding of the crack structure and aid in the formulation of subsequent treatment plans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated that AI-based deep learning methods, such as wavelet-guided deep models, can outperform human observers in terms of diagnostic accuracy [ 21 , 22 ]. While certain deep learning methods have been shown to provide a relatively high diagnosis rate (exceeding 90% using binary classification neural networks [ 20 , 24 ] as well as combined U-Net and YOLOv4 network [ 37 ]), issues such as extended detection time and limited crack information suggest that semantic segmentation methods may offer more detailed and specific information. This can facilitate a more comprehensive understanding of the crack structure and aid in the formulation of subsequent treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional small object detection, DeepLabv3 demonstrates significant advantages compared to FCN and U-Net model [ 58 ]. With improvements to the ASPP module and the fully connected conditional random field module, DeepLabv3+ has achieved even better results in terms of mandibular fractures detection [ 37 ], particularly in detecting smaller targets such as cracks in terms of over-segmentation and precision. Based on our experiments DeepLabv3+ performs best in tooth crack segmentation compared to other commonly used networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the diagnosis of mandibular fractures on panoramic radiographic (PR) images is quite difficult, CBCT imaging is preferred by radiologists and surgeons. To alleviate the unavailability of CBCT, Son et al (2022) combined two deep networks U-Net and YOLOv4 for detecting the location of mandibular fractures based on PR images without the use of CBCT. Another motivation of for the combination of the two deep networks was to minimize the number of likely undiagnosed fractures (symphysis, body, angle, ramus, condyle, and coronoid regions).…”
Section: Frontal-bone Fracturesmentioning
confidence: 99%
“…Compared to twostage object detectors, the models of YOLO series offer a more balanced combination of accuracy and inference speed, making them suitable for deployment on mobile computing platforms for medical image recognition. Son et al [28] utilized YOLOv4 [9] and U-Net [29] as auxiliary diagnostic tools to assist dentists in identifying mandibular fractures without resorting to cone beam computed tomography (CBCT). Jeon et al [30] employed YOLOv4 [9] to aid surgeons in diagnosing trauma by detecting the fracture and mapping it onto a 3D reconstructed bone image, providing a clear display of the fracture region through the red mask overlaid on the 3D bone image.…”
mentioning
confidence: 99%